Hereditary Fructose Intolerance - N.V. Nagornaya; Ye.V. Bordyugova; А.P. Dudchak; А.P. Koval (Zaslavsky O.Yu., 2014)
Hereditary fructose intolerance, the prevalence of which is 1 : 20,000 population, is diagnosed much less frequently than is found in child and adult populations. Presented pathology is caused by a deficiency in ferment aldolase B and block of fructose transformation in the gastrointestinal tract with the accumulation of unprocessed fructose in the intestine, manifesting by characteristic symptom and numerous biochemical changes in the body. The disease is asymptomatic until a person begins to use fructose, sucrose or sorbitol. This article describes the fructose metabolism, genetic aspects of the discussing disease, the diversity of its clinical manifestations. The authors presented modern diagnostic criteria and international approaches to diet therapy.